Worship Place and Delegitimization of Muslim Minorities in Indonesia: Insights from Indonesia - Hafidz, Hafidz; Karim, Abdul; Muhaimin, Muhaimin; Majeed, Muhammad Kashif (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
The phenomenon of delegitimization of minority Muslims has become a problem in religious life in Indonesia. Violence, intimidation and division are commonplace. This phenomenon will be seen from the point of view of analytic philosophy. This article aims to examine the chronology of the destruction of places of worship, the main causes of destruction, the inner experiences of the victims, and the pattern of conflict resolution that has been implemented. This article uses Wittgenstein's theory of truth claims, religious exclusivism, and language games. This study analyzes the roots of conflict, the mechanisms of delegitimization, and its impact on social cohesion. This study shows that the conflicts experienced by the Indonesia Institute of Islamic Dawah (LDII) are not solely triggered by doctrinal differences, but are the result of interactions between minority exclusivism, the claims of the majority's truth, social delegitimization, and the failure of inclusive dialogue. The accusation of heresy reflects the struggle for interpretive authority within the Muslim community. With Wittgenstein's framework of language games, differences in teachings are understood as expressions of different ways of life so that they cannot be the basis for misdirection. Therefore, conflict resolution demands an egalitarian dialogue that recognizes the plurality of religious experience and rejects claims of a single truth.